Direcionadores de governança para a sustentabilidade do negócio: análise sistêmica da mineração de carvão - Kadel Junior, Nelson (Universidade do Vale do Rio dos Sinos, 2023)
Mining has played a pivotal role in the construction of the roads that led the world's major powers to economic development. Simultaneously, coal has served as the engine driving this progress, providing an economical, efficient, and reliable source of energy. However, this achievement has also brought with it a significant environmental and social impact, affecting both the environment and society. The pursuit of sustainable development now occupies the center stage of international agreements as the world seeks solutions to mitigate the effects of climate change on societies without resulting in economic stagnation for countries. This duality between economic and environmental aspects is not exclusive to the international stage; it is also reflected in the economic policies of the State of Rio Grande do Sul, especially in the city of Candiota, the primary coal reserve in Brazil. In this context, this research aims to propose comprehensive sustainability governance guidelines that holistically address the Sustainable Development Goals (SDGs) as a means to promote a responsible agenda and secure the Social License to Operate (LSO). The local community represents the most significant stakeholder in the system, with its outcomes measured through Environmental, Social, and Governance (ESG) indicators. The use of Systems Thinking, through systemic transcription, was crucial in understanding the complex relationships between the various concepts investigated and in analyzing the recorded discourses of the identified stakeholders during data collection. The chosen research method for this study was Design Science Research (DSR), which contributed to a significant sequence of insights throughout the process and the construction of a comprehensive framework of knowledge. The result was the development of a model with eight systematically structured drivers aimed at promoting corporate governance in the pursuit of sustainability while contributing to practical outcomes, including efficient resource use, rehabilitation of impacted areas, social responsibility, assistance actions, workforce training and qualification, and behavior standards. The driver model was approved by experts, ensuring its validity and concluding that sustainability can be achieved more effectively through the adoption of responsible and efficient practices, including effective resource utilization, rehabilitation of impacted areas, social responsibility, and behavioral norms.
Keywords: Governança; Sustentabilidade; Pensamento sistêmico; Transcrição sistêmica; Governance; Sustainability; Systems thinking; Systemic transcription; ACCNPQ::Engenharias::Engenharia de Produção